The impact of electronic services technology in minimizing the phenomenon of job burnout in Commercial Bank of Syria - A. Alhannash; H.T. A. Abueissa; E. A. Khalimon (Управление)
The research aims to test the relationship between electronic service technology and job burnout among employees of the Commercial Bank of Syria, and to what extent modern technology contributes to reducing the negative manifestations of job burnout among workers in addition to the level of technology used in providing various banking services at the Commercial Bank of Syria. Testing the level of job burnout that bank employees are exposed to, and the study found an inverse relationship between electronic service technology and job burnout among workers. Therefore, modern technology contributed to alleviating the causes of this phenomenon by increasing flexibility in banking performance due to the ease of use of this technology and reducing errors committed by employees. It is shown, that the bank does not have the latest technology, which covers all banking services, so that all of them can be provided electronically. As for job burnout, it was noted that there was a low job burnout experienced by workers in the Commercial Bank of Syria, but there was suffering on the part of some workers in facing the problems they are exposed to, and the research concluded with a set of recommendations for the Commercial Bank of Syria in line with the results that were reached through research.